2010
DOI: 10.1590/s1413-86702010000200006
|View full text |Cite
|
Sign up to set email alerts
|

Signal to cut-off (S/CO) ratio and detection of HCV genotype 1 by real-time PCR one-step method: is there any direct relationship?

Abstract: Background: Polymerase chain reaction (PCR) methods play an essential role in providing data related to diagnosis, monitoring and treatment of hepatitis C virus (HCV) infection. EIA results are reported as "reactive" or "non reactive" and EIA S/CO ratio may also be reported as "high" or "low." This study aimed to evaluate the performance of a real-time RT-PCR and assess whether there is relationship between S/CO and PCR results. Study Design and Methods: Sera from blood donors were analyzed by Enzyme-Linked Im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Amplification was performed using a 7500 Real-Time Sequence Detection System (SDS; ABI Prism 7500; Applied Biosystems, CA). RT-PCR product accumulation was monitored using a TaqMan probe 3940.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Amplification was performed using a 7500 Real-Time Sequence Detection System (SDS; ABI Prism 7500; Applied Biosystems, CA). RT-PCR product accumulation was monitored using a TaqMan probe 3940.…”
Section: Methodsmentioning
confidence: 99%
“…Dilutions of this standard were tested with a total of 24 replicates for each point dilution to determine the positive cut-off point or lower limit of detection. RT-PCR product accumulation was monitored using a TaqMan probe 3940.…”
Section: Methodsmentioning
confidence: 99%
“…The increasingly sophisticated methods of diagnosing HCV infection have a direct impact on patient management and the use of more sensitive and specific assays is essential for an efficient diagnosis of HCV infection (Albertoni et al, 2010). Several seroprevalence studies have indicated that S/Co ratios could be used to accurately predict a positive status in conjunction with a confirmatory test Centers for Disease Control and Prevention, 2003;Dos Santos et al, 1999;Tobler et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Several seroprevalence studies have indicated that S/Co ratios could be used to accurately predict a positive status in conjunction with a confirmatory test Centers for Disease Control and Prevention, 2003;Dos Santos et al, 1999;Tobler et al, 2000). Although the majority of the seroprevalence studies reported were performed using the commercially available EIA test (Centers for Disease Control and Prevention, 2003;Dos Santos et al, 1999;Tobler et al, 2000;Albertoni et al, 2010), in the present study we utilized VITROS anti-HCV assay, whose performance was evaluated in some previous published studies. As reported by Ismail et al (2004), we also found, in the S/Co range of between 1 and 8, EIA negative/CIA positive samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation